The Mercosur in the midst of the crisis - Cruz, Dayana Aparecida Marques de Oliveira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
Since 2016, the four States Parties to the Southern Common Market (Mercosur) - Argentina, Brazil, Paraguay and Uruguay - are experiencing internal political and economic crises that cannot be understood without observing the South American regional context. With the pandemic of the new coronavirus, the crisis also took on a health dimension, whose repercussions in 2021 made the celebration of the bloc’s thirty years a moment of reflection on the effectiveness of the integration process, due to the absence of territorial management that addresses the Mercosur needs. The purpose of this text is to discuss the measures adopted in the context of Mercosur in the face of the current pandemic, economic and political crisis. The methodology used for the elaboration of the text included a bibliographic review on the regional integration process in Mercosur and the analysis of news about the situation and the measures adopted to contain the effects of the crisis in Argentina, Brazil, Paraguay and Uruguay.